2021
DOI: 10.3126/tujm.v8i1.41198
|View full text |Cite
|
Sign up to set email alerts
|

Antibiogram and Biofilm Development among Klebsiella pneumoniae from Clinical Isolates

Abstract: Objectives: This study was aimed to evaluate antibiotic resistance pattern and biofilm formation in K. pneumoniae strains isolated from different clinical specimens and to study on association of drug resistance pattern with biofilm formation. Methods: A total of 944 clinical samples from patients attending Sahid Gangalal National Heart Center were processed from September 2019 to March 2020 to identify possible bacterial pathogens following standard microbiological procedures. K. pneumonaie isolates were furt… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 0 publications
1
1
0
Order By: Relevance
“…The study showed that MEM was considered more effective than IMI, which 33% of samples resistant to IMI (MIC of >1024 µg/mL). These results are consistent with a study by Subash et al, who reported that the sensitivity of Gram-negative bacilli to MEM is more than IMI due to the overuse of the latter antibiotic (for many years) as an empirical treatment option [ 34 ].…”
Section: Resultssupporting
confidence: 93%
“…The study showed that MEM was considered more effective than IMI, which 33% of samples resistant to IMI (MIC of >1024 µg/mL). These results are consistent with a study by Subash et al, who reported that the sensitivity of Gram-negative bacilli to MEM is more than IMI due to the overuse of the latter antibiotic (for many years) as an empirical treatment option [ 34 ].…”
Section: Resultssupporting
confidence: 93%
“…Biofilms defined as bacterial aggregations attached to a surface and to each other and embedded in a self-produced structure composed of proteins (for example, fibrin), polysaccharides (for example, alginate), and extracellular DNA [6]. Biofilm is an important feature that aid pathogens avoiding host immune responses, survive at high levels of antibiotics, and establish a chronic infection.…”
Section: Introductionmentioning
confidence: 99%